Oral Cavity: A Forensic Kaleidoscope - Darwin, Deepthi; Sakthivel, Soundarya; Castelino, Renita Lorina; Babu, Gogineni Subhas; Asan, Mohamed Faizal; Sarkar, Anand Shankar (Journal of Health and Allied Sciences NU, 2021)
Forensic odontology is an integral part of the multidisciplinary field of forensic sciences that requires specialized training and perceptive knowledge for its application in full potential. Forensic odontology deals with the evidence pertaining to the oral and paraoral structures. Dentists are equipped with knowledge of orofacial structures and their variations prevailing among different ancestry. By implicating the history of dental treatments to the identification process, dentists extract unique and accurate information that aids in forensic identification. Crimes such as child abuse and domestic violence are often identified by the dentists during routine dental examinations and this can be used as an evidence to discern malefactors in such cases. This article provides a collective review of applications and methods in forensic odontology that helps legal authorities in the identification of individuals.
Keywords: forensic dentistry; disaster victims; inventions; dental prosthesis; three-dimensional printing